In-water resisted sprint swim training for age-group swimmers - Kojima, K.; Brammer, C. L.; Sossong, T. D.; Abe, T.; Stager, J. M. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Worldwide, coaches employ training paradigms in an effort to maximise the performances of their athletes. In competitive swimming, a variety of methods have evolved as a means to improve swim performance, all of which focus on increasing swimmers' abilities to develop propulsive force, decrease drag forces, or some combination of these factors. One accepted method used to improve propulsive force is an increase muscle size and function. There is some support that land-based resistive exercise increases muscle size, improves muscle function, and enhances motor skills with children and adolescents (Behringer et al. 2010; Harries et al. 2012). However, whether or not landbased resistive training enhances sport performance remains inconclusive in young athletes, due primarily to methodological and logistical discrepancies among previous studies. Further, land exercise does not commonly replicate actual swim movements, thus the extent to which it is useful in improving swim performance may be limited. Specific training methods would, at least theoretically, increase the likelihood of improving performance outcomes. Swim power or 'in-water' resisted sprint swim training (IWRST) has been acknowledged by scientists and coaches to enhance sprint swim performance due to the specificity of training. Typical IWRST requires a cable connected to a spring balance scale (Julian & Coltune 1958), a rack-pulley system (Hopper 1975), or an elastic cord (Girold et al. 2007) whereby a swimmer is attached via a waist belt to the resistive load while swimming. IWRST has been previously suggested to invoke positive effects on adult swimmers (Aspenes & Karlsen 2012; Tanaka & Swensen 1998). Only one study has reported the use of IWRST in late adolescents (Girold et al. 2007). Studies using similar training paradigms with pre- or peri-adolescent (age-group) swimmers do not appear to exist. The limited prevalence of research regarding IWRST in age-group swimmers may be attributable to the limited availability of training devices and/or other specialised equipment. More importantly, the lack of information regarding practical use and the efficacy of such training with age-group swimmers is likely an added deterrent. Whether or not IWRST, specific to age-group swimmers who are already actively training, is effective and advisable is currently dependent upon speculation. Therefore, data describing the benefits, or lack thereof, of IWRST in the adolescent population are needed. The purpose of this study was to examine the efficacy of IWRST on sprint swim performance and muscle mass in age-group swimmers when compared with traditional non-resisted sprint swim training.